Samples of translation of Alisher Navoi's aphorisms into English and problem of their translation - Geldiyeva Khursandoy (Genius Journals, 2022)
We all know that Alisher Navoi is a world-famous scholar who always tries to translate their unique works into all languages. Today, Alisher Navoi's works are loved and listened to not only by the peoples of the East, but also by the West. To date, Navoi's works have been translated into Russian, English, German, French and many other languages. Through these translations, all nations will enjoy such a great and priceless heritage, and in some countries even statues of Alisher Navoi have been erected as a symbol of love. This article also contains some of the wisdom of our great scholar in the work "Mahbub ul-qulub". It also provides information on the problems encountered in the translation of Navoi's works, brief solutions, and differences in Eastern and Western literature.
Keywords: Works; Eastern Literature; Western Literature; Proverbs